Equilibration Times of Dissolved Inorganic Carbon During pH Transitions - Sade, Ziv; Hegyi, Shahar; Halevy, Itay (Frontiers in Earth Science, 2022)
Equilibration times of dissolved inorganic carbon (DIC) depend on conversion reactions between CO2(aq) and the dissociation products of carbonic acid [S = (H2CO3) + (HCO3−) + (CO32−)]. Here, we develop analytical equations and a numerical model to calculate chemical equilibration times of DIC during pH transitions in buffered and unbuffered solutions. We approximate the equilibration degree of the DIC reservoir by the smaller of the CO2(aq) and S pools at the new pH, since the smaller pool is always farther from equilibrium during the chemical evolution. Both the amount of DIC converted and the rate of conversion differ between a pH increase and decrease, leading to distinct equilibration times for these general cases. Alkalinity perturbations in unbuffered solutions initially drive pH overshoots (increase or decrease) relative to the new equilibrium pH. The increased rates of DIC conversion associated with the pH overshoot yield shorter equilibration times compared to buffered solutions. Salinity has opposing effects on buffered and unbuffered solutions, decreasing and increasing equilibration times, respectively.